Analysis of Embankment Slope Failure And Effectiveness Of Reinforcement With Full Displacement Column on Soft Soil (Case Study : Construction Of Padang Sicincin Toll Road Section STA 7+400 – 7+550) - Arifanto, Firman; Satrya, Trihanyndio Rendy; Soemitro, Ria Asih Aryani; Hardiningsih, Sri Hastuti (Journal of Infrastructure & Facility Asset Management, 2024)
The package that is currently under construction on the Trans Sumatra toll road network section Padang - Pekanbaru is the Padang - Lubuk Alung - Sicincin section which is targeted for completion in July 2024. One of the obstacles in the work process is that there is an embankment landslide at STA 7 + 450 which is indicated due to a decrease in the subgrade. This resulted in the construction process not being able to continue so there was a delay in the progress of construction implementation. Therefore, a study is needed that focuses on analyzing the causes of landslides and follow-up recommendations to overcome problems in the STA 7 + 450 embankment work on the Padang - Pekanbaru Toll Road Construction project section Padang - Lubuk Alung - Sicincin. The method used in this research is finite element modeling analysis using the help of the PLAXIS 2D program by looking at the Safety Factor value of the embankment slope under initial conditions and back analysis. The landslide modeling results with the finite element method are also compared with the landslide lines that occur in the field. From the back analysis, new parameters are obtained when a landslide occurs as input in the reinforcement analysis to be used. For follow-up improvement, full displacement column reinforcement is proposed where the effect of FDC column spacing, thickness, and load transfer platform material combination on slope stability, settlement, and changes in soil mechanical parameters will be analyzed. It was found that the embankment structure before the collapse had a critical SF value of SF = 1.010. The cause of the landslide was indicated to be due to the additional load from the project vehicle traffic. Parameter changes were obtained in the form of c' = 8.17 kN/m2 and Ø' =19.68o, cc = 0.8175, and cs =0.1204 in the organic soft soil which was indicated to be the cause of the landslide. From the modeling results to find the effectiveness of reinforcement with FDC, the optimum parameters were obtained concerning a distance of 3 times the column diameter, and a Load Transfer Platform thickness of 1.8 meters with geogrid reinforcement.